Moving A Nation: The Evolution of Public Transit in Indonesia - Enhanced Analysis - I Made Suartika (Jurnal Pendidikan Indonesia, 2025)
This study examines the evolution of Indonesia’s public transportation system as a reflection of its national development journey, from the colonial period to the modern era of innovation and sustainability. The research focuses on the role of public transport in enhancing connectivity, reducing socio-spatial inequalities, and supporting economic growth. Using a qualitative descriptive approach based on literature review and recent empirical data, the findings reveal that public transport plays a strategic role in improving mobility equity, economic efficiency, and carbon emission reduction. Major transformations have occurred through the implementation of the Bus Rapid Transit (TransJakarta) system, development of MRT and LRT networks, and digital innovations in payment and data integration. However, persistent challenges remain in accessibility gaps, modal integration, and financial sustainability. The study concludes that the success of Indonesia’s public transport relies on multi-sector collaboration, evidence-based policy, and the application of inclusive and sustainable mobility principles to achieve equitable and competitive urban transport.